Postnational Musical Identities: Cultural Production, Distribution, and Consumption in a Globalized Scenario - Corona, Ignacio,; Madrid, Alejandro L., (Lexington Books, 2007)
Postnational Musical Identities gathers interdisciplinary essays that explore how music audiences and markets are imagined in a globalized scenario, how music reflects and reflects upon new understandings of citizenship beyond the nation-state, and how music works as a site of resistance against globalization. 'Hybridity,' 'postnationalism,' 'transnationalism,' 'globalization,' 'diaspora,' and similar buzzwords have not only informed scholarly discourse and analysis of music but also shaped the way musical productions have been marketed worldwide in recent times. While the construction of identities occupies a central position in this context, there are discrepancies between the conceptualization of music as an extremely fluid phenomenon and the traditionally monovalent notion of identity to which it has historically been incorporated. As such, music has always been linked to the construction of regional and national identities. The essays in this collection seek to explore the role of music, networks of music distribution, music markets, music consumption, music production, and music scholarship in the articulation of postnational sites of identification.